2020
DOI: 10.3892/ol.2020.11501
|View full text |Cite
|
Sign up to set email alerts
|

A challenging therapeutic method for breast cancer: Non‑lipolytic endoscopic axillary surgery through periareolar incisions

Abstract: Surgical treatment of breast cancer is becoming increasingly precise, less invasive, and more cosmetically pleasing. Sentinel lymph node biopsy (SLNB) and axillary lymph node dissection (ALND) remain the standard treatment methods for breast cancer. However, these methods still require incisions in the breasts or axilla. Mastoscopic axillary lymph node dissection (MALND) surgery, although first reported several years ago, has not been widely used as it involves lipolysis. Non-lipolytic mastoscopy may be more a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…Luo et al [ 11 ]e compared 500 patients with MRM and 496 patients who underwent mastoscopy and showed that mastoscopy had advantages in terms of healing, complications, function preservation, and cosmetics. These results are supported by other studies [ 14 , 19 , 20 ]. Mastoscopic glandectomy shares some principles with skin-sparing mastectomy, which is associated with good esthetic and oncological outcomes [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Luo et al [ 11 ]e compared 500 patients with MRM and 496 patients who underwent mastoscopy and showed that mastoscopy had advantages in terms of healing, complications, function preservation, and cosmetics. These results are supported by other studies [ 14 , 19 , 20 ]. Mastoscopic glandectomy shares some principles with skin-sparing mastectomy, which is associated with good esthetic and oncological outcomes [ 21 , 22 ].…”
Section: Discussionsupporting
confidence: 92%
“…Those good outcomes are comparable to those achieved using classical mastoscopic surgery [ 11 , 12 , 14 , 19 , 20 ], Ding et al [ 12 ] randomized 60 patients to mastoscopic SLNB, conventional SLNB, and SLNB with lipolysis and showed that mastoscopic SLNB performed at least as well than conventional SLNB. Luo et al [ 11 ]e compared 500 patients with MRM and 496 patients who underwent mastoscopy and showed that mastoscopy had advantages in terms of healing, complications, function preservation, and cosmetics.…”
Section: Discussionmentioning
confidence: 74%
“…In our study, estrogen receptor was expressed among patients (72.2%) and Progesterone receptor was positive in (66.7%) patients, while Human epidermal growth factor receptor/2 was expressed among (16.7%) patients in agreement with Chen et al (14) who reported that estrogen receptor was Positive in (62.5%) and Progesterone receptor was Positive in (62.5%) while Human epidermal growth factor receptor/2 was expressed only in (12.5%). Bordoni et al (6) also reported 64.8% were positive for estrogen and progesterone receptors and 16% were positive for Human epidermal growth factor receptor/2.…”
Section: Discussionsupporting
confidence: 91%
“…Supporting our results Foissac et al (4) reported all cases had ductal carcinoma with a majority of grade I (50%) and II (26.6%) infiltrating ductal carcinoma. Furthermore Chen et al (14) reported the Histological types of breast cancer in study participants were 14 out of 16 had invasive ductal carcinoma (87.5%) and one case mucinous breast cancer and one case ductal carcinoma in situ. and this goes with the fact that Ductal Carcinoma is more prevalent than other variants.…”
Section: Discussionmentioning
confidence: 98%
“…In 1990, Benelli [ 17 ] first described a whole-circumareolar incision for mammoplasty, the so-called round block technique or Benelli mastopexy. The advantages of the periareolar incision include not only a less-visible scar but also wider exposure to the deepithelized skin and its usefulness in tumors located in any quadrant of the breast [ 18 19 20 ]. In addition, incision closure can usually be performed using the continuous cerclage suture technique.…”
Section: “Aesthetic Scar-less” Breast-conserving Surgerymentioning
confidence: 99%